2008
DOI: 10.1364/oe.16.013676
|View full text |Cite
|
Sign up to set email alerts
|

Tunable single-mode photonic lasing from zirconia inverse opal photonic crystals

Abstract: Lasing from zirconia inverse opal photonic crystal structures infiltrated by solutions of rhodamine dyes was found to exhibit single-mode lasing peaks with spectral width less than 1 nm and quality factor in excess of 4000. The lasing occurs within the approximate range of high-reflectance spectral region associated with photonic stop band along [111] crystallographic direction, but its wavelength is not fixed to the corresponding Bragg wavelength of the periodic structure, and depends on the spectral position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…The Förster energy transfer in a higher refractive index contrast 3D photonic structures with photonic stop gap could further enhance the energy transfer when the donor emission is forbidden by the stop gap and a single-mode lasing is realized (Nishijima et al, 2008). The spectral positions of the lasing modes were stable at the all range of employed laser pumping powers.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The Förster energy transfer in a higher refractive index contrast 3D photonic structures with photonic stop gap could further enhance the energy transfer when the donor emission is forbidden by the stop gap and a single-mode lasing is realized (Nishijima et al, 2008). The spectral positions of the lasing modes were stable at the all range of employed laser pumping powers.…”
Section: Resultsmentioning
confidence: 95%
“…This type of lasing is not defined by the photonic band gap because of the low refractive index contrast between silica (1.46) and ethylene glycol (1.42) (Kitamura et al, 2007;Nishijima, 2009;Nishijima et al, 2009a). Rather, it is determined by the distributed feedback (DFB) in the dye as demonstrated recently (Nishijima et al, 2008). The lasing threshold and the onset of lasing were determined from the power dependence of the lasing spectrum shown in Figure 7B.…”
Section: Figure 5 | Sem Images and Their 2d-fft Together With The Optmentioning
confidence: 87%
See 1 more Smart Citation
“…Therefore, transition metal oxides are also ideal alternative materials to prepare inverse opal 3DPCs. Many research groups including ours reported the fabrication of zirconia or yttria-stabilized zirconia (YSZ) with inverse opal structures that were obtained by filling a template of colloidal crystals with a sol or solution of zirconia or YSZ [16][17][18][19][20][21][22][23][24][25][26]. However, no noticeable reflection peak was observed in these reports.…”
Section: Introductionmentioning
confidence: 99%
“…Lasing from photonic crystals has been extensively studied by infiltrating the solutions containing dye molecules or semiconductors into them [9][10][11][12][13]. To date, numerous reports have confirmed optical modifications using two-dimensional (2D) and 3D photonic crystals [3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%